Consensus guidelines and recommendations for infection prevention in multiple myeloma: a report from the International Myeloma Working Group. Issue 2 (February 2022) - Raje, Noopur S; Anaissie, Elias; Kumar, Shaji K; Lonial, Sagar; Martin, Thomas; Gertz, Morie A; Krishnan, Amrita; Hari, Parameswaran; Ludwig, Heinz; O'Donnell, Elizabeth; Yee, Andrew; Kaufman, Jonathan L; et al.
Summary: Infection remains the leading cause of morbidity and mortality in patients with multiple myeloma because of the cumulative effect of disease, treatment, and host-related factors. Given that infectious risk is cumulative through the course of the disease, preventing infections is paramount. Optimal preventive strategies include vaccination against common pathogens, antimicrobial prophylaxis, infection control measures, and immunoglobulin replacement in a small subset of patients; however, there are no universally accepted guidelines for infection prevention. This Review provides a consensus statement from a panel of 36 experts with global representation, which was convened by The International Myeloma Society to review existing literature and current guidelines, address issues associated with the risk of infection and prevention of infectious complications in multiple myeloma in the context of emerging therapies, and offer recommendations for preventing these complications.